molecular diagnosis of new reassortant infctious bursal disease virus in broiler chicken - Ammar Dhari Abdel Fattah; Samer Sadeq Hameed (University of Thi-Qar Journal of agricultural research, 2024)
Infectious bursal disease, causing immunosuppression in chickens, poses significant financial challenges to the poultry sector. The onset of clinical symptoms and viral shedding is influenced by factors such as age, immunological condition, route of infection, and virus type. In this study, one hundred suspected infectious bursal disease (IBD) cases from nineteen chicken farms were examined, resulted in an overall positive rate of approximately 80%. Clinical signs in affected birds included ruffled feathers, decreased appetite, diarrhea, and a dirty vent, with hemorrhage seen on thigh muscles. Identification was done based on molecular methods, polymerase chain reaction (PCR), and gross pathological observations. Ten samples were randomly selected and tested using specific IBD primers. All those samples were positive, despite the absence of a known cure for IBD, preventive measures, including immunization and rigorous biosecurity protocols, can help mitigate its impact. The study underscores the importance of molecular techniques by using special Primer Design for diagnosing reassortant very virulent IBDv sttain in natural infected broiler in Iraq(data don’t mention). offering insights into its prevalence and the effectiveness of preventive measures.